Synergizing Sports Education and Urban Development: A Comprehensive Study of Industry-City-Education Integration in Yunnan’s Higher Vocational Colleges - Wang, Sheng; Nie, ZhenXin (Journal of Ecohumanism, 2024)
The study aims to evaluate the concept of sports education and urbanization in Yunnan by focusing more on the vocational institutions. The study directs the evaluation and the level of connection between the sports education of vocational education and its impact over the urban development of the province. To achieve this aim, the qualitative study has been conducted where the topic is studied by identifying some key articles as part of the secondary analysis. The secondary study offers insight into the level of adaption of sports education in the curriculum of Yunnan's vocational institutions and their role in the urban development to identify their linkage with the backup of the concept linked to Industry-city-education integration. The role of the education of sports is evaluated in the context of the role of vocational institutions based on Yunnan to deliver output that can improve social infrastructure. The key findings revealed that there are very few technical or vocational institutions in Yunnan that are offering sports education while many are focused on avoiding this practice and be more focused on the theoretical and course work material, along with this the vocational institutions are also not much into urbanization of Yunnan therefore it offers the confirmation of the literature that sports education integration give rise to the city development by practice of urbanization.The whole study concludes that the role of sports education is surely productive, and Yunnan must adapt it to move more towards urbanization because its current level of urbanization is very low.